Proses Pembelajaran dan Asesmen yang Efektif - Ali Ramatni; Fivie Anjely; Didik Cahyono; Saparuddin Rambe; Muwafiqus Shobri (Journal on Education, 2023)
Effective learning is learning that can successfully achieve a learning goal from students in accordance with what is expected by educators or teachers. An effective learning model is a learning model that includes four dimensions, namely: (1) Quality or quality of a learning, (2) adequate and relevant level of learning, (3) reward or reward or the provision of gifts from students to students, and (4) time, efficient classroom management also affects learning effectiveness. While effective assessment is a process to determine the achievement of students towards learning that has been carried out thoroughly. The assessment cycle can run effectively if the assessment is carried out continuously, through day-to-day assessment and periodic assessment. Day-to-day assessment can be done as an insert in the learning process; observation, discussion, Q&A and analyzing student work. While this periodic assessment is an assessment that is carried out periodically.